2018
DOI: 10.1016/j.juro.2017.09.147
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Ureteropelvic Junction Obstruction Using Signal Analysis and Machine Learning: A Dynamic Solution to a Dynamic Problem

Abstract: Our machine learning framework significantly improved the diagnostic accuracy of clinically significant hydronephrosis compared to half-time and 30-minute clearance. This aids in the clinical decision making process by offering a tool for earlier detection of severe cases and it has the potential to reduce the number of diuresis renograms required for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Blum et al. trained an ML model using renogram features to automatically detect hydronephrosis. The study showed that the ML model significantly improved the diagnostic accuracy of clinically significant hydronephrosis compared with looking only at half‐time and 30‐min clearance.…”
Section: Application Of Ai In Urologymentioning
confidence: 99%
See 1 more Smart Citation
“…Blum et al. trained an ML model using renogram features to automatically detect hydronephrosis. The study showed that the ML model significantly improved the diagnostic accuracy of clinically significant hydronephrosis compared with looking only at half‐time and 30‐min clearance.…”
Section: Application Of Ai In Urologymentioning
confidence: 99%
“…Imaging radiomic features and AI algorithms have also been applied to detect clinically significant hydronephrosis or urinary reflex. Blum et al [18] trained an ML model using renogram features to automatically detect hydronephrosis.…”
Section: Hydronephrosis/urinary Refluxmentioning
confidence: 99%
“…MAG3 uptake and drainage were identified and defined by O'Reilly et al [20], usually, the time consumed for clearance of 50% (t½) of the garnered radionuclide is <10 min, whereas a t½ of >20 min is indicative, but not diagnostic, of obstruction. Blum et al [21] studied renograms of 55 patients and proposed that better (t½) has an accuracy of 83% when used for 24.5 minutes. A study published on adult laparoscopic pyeloplasty reported t½ near 14 [17], whereas the present study found t½ up to 7.85 among the laparoscopic group and 9 in the open pyeloplasty group at one year.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that SVM gives better results (AUC greater than 0.9) than the other tested methods. Blum et al (2018) used SVM on a data set of diuresis renogram recorded on 55 patients to predict uteropelvic junction obstruction.…”
Section: Re Vie W On Machine Le Arning Appli C Ati On S For Pred I mentioning
confidence: 99%